(untitled) (Conferencea, 2024)
This thesis analyzes the interrelationship between financial technologies and the international financial market. The role of financial technologies in increasing the efficiency of financial services, the segments of the international financial market and their contribution to their development, as well as the prospects for the development of financial technologies in the context of Uzbekistan are highlighted. In order to improve the economic development of our country, it is highlighted that the issues of improving the financial system and achieving high macroeconomic indicators are of great importance, and the President of the Republic of Uzbekistan “On additional measures for the transition to international standards of financial reporting”, the requirements of decision PD-4611 of February 24, 2020 are stated. The thesis examines ways of increasing the country’s economic stability through the use of international experiences and the analysis of global trends in the field of financial technologies.